Translating time : cinema, the fantastic, and temporal critique - Lim, Bliss Cua (e-Duke books scholarly collection., 2009)
"Under modernity, time is regarded as linear and measurable by clocks and calendars. Despite the historicity of clock-time itself, the modern concept of time is considered universal and culturally neutral. What Walter Benjamin called "homogeneous, empty time" founds the modern notions of progress and a uniform global present in which the past and other forms of time consciousness are seen as superseded. In Translating Time, Bliss Cua Lim argues that fantastic cinema depicts the coexistence of other modes of being alongside and within the modern present, disclosing multiple "immiscible temporalities" that strain against the modern concept of homogeneous time. In this wide-ranging study - encompassing Asian American video (On Cannibalism), ghost films from the New Cinema movements of Hong Kong and the Philippines (Rouge, Itim, Haplos), Hollywood remakes of Asian horror films (Ju-on, The Grudge, A Tale of Two Sisters) and a Filipino horror film cycle on monstrous viscera suckers (Aswang) - Lim conceptualizes the fantastic as a form of temporal translation. The fantastic translates supernatural agency in secular terms while also exposing an untranslatable remainder, thereby undermining the fantasy of a singular national time and emphasizing shifting temporalities of transnational reception."--Publisher's description